2015
DOI: 10.2147/opth.s90322
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal pegaptanib for the treatment of ischemic diabetic macular edema

Abstract: PurposePegaptanib has been shown to be effective in treating diabetic macular edema (DME). In the original Phase II/III trial, however, patients with macular ischemia were excluded. In this study, we treated patients with ischemic DME.MethodsMacular ischemia was defined as a 30% increase in the area of the foveal avascular zone (FAZ) at 45 seconds on fundus fluorescein angiography. In addition, the participants had diffuse foveal-involving DME with a central subfield thickness (CST) of >300 μm on spectral-doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…It is worth noting that Macugen is chemically modified and contains both 2′-F and 2′-OMe modifications and the attachment of a 40-kDa polyethylene glycol. 49 Macugen is also lately explored for its application in diabetic macular edema, 50 ischemic diabetic macular edema 51 and myopic choroidal neovascularization. 52 Recently, a new monoclonal antibody (ranibizumab, Novartis) drug was approved by FDA in 2015 and is now in clinical use to compete with Macugen.…”
Section: Discussionmentioning
confidence: 99%
“…It is worth noting that Macugen is chemically modified and contains both 2′-F and 2′-OMe modifications and the attachment of a 40-kDa polyethylene glycol. 49 Macugen is also lately explored for its application in diabetic macular edema, 50 ischemic diabetic macular edema 51 and myopic choroidal neovascularization. 52 Recently, a new monoclonal antibody (ranibizumab, Novartis) drug was approved by FDA in 2015 and is now in clinical use to compete with Macugen.…”
Section: Discussionmentioning
confidence: 99%
“…The common strategies in the chemical modifications of nucleic acid aptamers and their purposes. Among the modifications, such as modifications on the terminals of nucleic acids, modifications on the phosphodiester linkage, modifications on the sugar ring and modifications on the bases, the 3′ end capping with inverted thymidine [6,12] and PEGylation [13] have been the common strategies in the chemical modifications of nucleic acid aptamers for development clinical therapeutics [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Then, the chemical modification strategies of aptamers for resisting nuclease degradation [12,[20][21][22][23][24][25][26], improving target binding affinities [10,[27][28][29][30][31] and resisting renal clearance [32][33][34][35][36] will be summarized, sequentially. Among the modifications, such as modifications on the terminals of nucleic acids, modifications on the phosphodiester linkage, modifications on the sugar ring and modifications on the bases, the 3′ end capping with inverted thymidine [6,12] and PEGylation [13] have been the common strategies in the chemical modifications of nucleic acid aptamers for development clinical therapeutics (e.g., pegaptanib [14][15][16][17], etc.). More excitingly, aptamers with improved binding affinities are being generated with modifications on the bases [29] or substitutions of two non-bridging phosphate oxygen atoms in nucleic acids by sulfur replacement [10] (see "SOMAmers" and "PS2 walk" below).…”
Section: Introductionmentioning
confidence: 99%
“…Additional studies have also shown similar results, with improvements in visual or anatomical outcomes [ 73 , 74 , 75 , 76 ]. However, due to the drug’s low clinical efficacy in comparison to other anti-VEGF medications, it is utilized considerably less often in clinical practice [ 77 ].…”
Section: Current Therapeuticsmentioning
confidence: 99%